Evaluation of Total Phenolics, Total Flavonoids, Antioxidant Capacity and Antimicrobial Activity of Herbal Extracts in Thai Traditional Medicine Recipes - Sirisom, Nattida; Khongphakdee, Thipthanya; Supaphon, Preuttiporn (Journal of Advanced Development in Engineering and Science, 2025)
This research aims to assess the potential of six herbal species in Thai traditional medicine recipes for inhibiting pathogenic microorganisms and combating free radicals. Additionally, the total phenolic and total flavonoid contents of the extracts were analyzed using the Folin-Ciocalteu method and colorimetric aluminum chloride, respectively. Preparing the extracts from six herbal plants (Drypetes roxburghii, Cleome viscosa, Blumea balsamifera, Glycosmis pentaphylla, Rhinacanthus nasutus and Curcuma zedoaria) using ethanol and ethyl acetate as solvents. Subsequently, the effectiveness of the extracts in inhibiting microorganisms and their antioxidant activity was assessed using colorimetric broth microdilution and DPPH radical scavenging assays, respectively. The results indicated that extracts from each herbal species effectively inhibited nine pathogenic microorganisms and exhibited strong antioxidant properties. The ethanol extracts from D. roxburghii and C. viscosa showed the best inhibition against Staphylococcus epidermidis and Taralomyces marneffei, with a minimum inhibitory concentration (MIC) of 50 µg/mL. Furthermore, the antioxidant assays revealed that the ethanol extracts from D. roxburghii and C.viscosa had the highest DPPH inhibition values of 15.32 ± 0.38 and 24.75 ± 0.97 µg/mL. Furthermore, the highest total phenolic content was found in the ethanol extract from D. roxburghii and C. viscosa at 82.20 ± 0.56 and 124.98 ± 0.74 mg gallic acid equivalent/g extract, respectively. This study suggests that each herbal species in traditional Thai medicinal recipes is a potential sources of bioactive compounds.